2013
DOI: 10.1038/ncomms2724
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin−SNARE interactions control trans-SNARE formation in intracellular membrane fusion

Abstract: The fundamental processes of membrane fission and fusion determine size and copy numbers of intracellular organelles. While SNARE proteins and tethering complexes mediate intracellular membrane fusion, fission requires the presence of dynamin or dynamin-related proteins. Here we study these reactions in native yeast vacuoles and find that the yeast dynamin homolog Vps1 is not only an essential part of the fission machinery, but also controls membrane fusion by generating an active Qa SNARE- tethering complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…We also confirm that these stimuli have the opposing effect on homotypic vacuole fusion, lending additional support to the idea that fission and fusion are highly coordinated (e.g. Alpadi et al, 2013). This is a requirement for efficient changes in morphology, whereby if fission occurs, the counteracting process of fusion must be blocked for the organelle to remain fragmented, i.e.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…We also confirm that these stimuli have the opposing effect on homotypic vacuole fusion, lending additional support to the idea that fission and fusion are highly coordinated (e.g. Alpadi et al, 2013). This is a requirement for efficient changes in morphology, whereby if fission occurs, the counteracting process of fusion must be blocked for the organelle to remain fragmented, i.e.…”
supporting
confidence: 61%
“…These findings have led to the idea that the 30 underlying machinery is highly integrated (e.g. LaGrassa and Ungermann, 2005;Alpadi et al, 2013). The basis of homotypic vacuole fusion has been resolved with incredible molecular precision (see Wickner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6F) (Thorngren et al, 2004). Whether the observed requirement of Vps1 for membrane fusion (Alpadi et al, 2013;Kulkarni et al, 2014;Peters et al, 2004) relates to either a fusion-specific function or rather to a consequence of a defect in recycling, needs further investigation. Our data show that the fusion defect applies to both retromer and vps1 mutants, even though the fusion machinery is apparently present on vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Vps1 has been previously linked to vacuole biogenesis and was shown to affect not only vacuole fission but also fusion (Alpadi et al, 2013;Peters et al, 2004). The vps1D mutant has a defect in in vitro vacuole fusion, and recombinant Vps1 interacts with the SNARE Vam3 (Peters et al, 2004).…”
Section: The Retromer and Vps1 Affect Vacuole Homeostasismentioning
confidence: 99%
“…In yeast, the dynamin homolog Vps1p interacts with the t-SNARE Vamp3; the disruption of this association with an antibody against Vps1p inhibits the fusion reaction (82). More recently, Peters’ lab has demonstrated that Vps1 binds to the Qa SNARE Vamp3 and controls trans-SNARE formation, which is essential for membrane fusion in yeasts (83). …”
Section: Dynamin As a Facilitator Of Membrane Fusionmentioning
confidence: 99%